LAKE ISSYK-KUL (TIEN SHAN): UNUSUALLY LOW HEAT FLOW IN AN ACTIVE INTERMONTANE BASIN - Vermeesch P.; Poort J.; Duchkov A.D.; Klerkx J.; Batist M.De. (My University, 2004)
New geothermal data are presented for Lake Issyk Kul’, a mountain lake in the northern Tien Shan, Central Asia. With 40 successful measurements done, the average heat flow is 48.3 mW/m 2 . This is 10 to 20 mW/m 2 lower than estimates from previous surveys. Data from boreholes on the shores of the lake revealed an average heat flow of 54 mW/m 2 . All these values are remarkably low for an actively deforming area such as the Tien Shan. Two qualitative geodynamical models are suggested to explain these observations. If there is crustal thickening beneath Issyk Kul’, the low heat flow can only be explained in a transient mode, with “sawtooth geotherm”. In equilibrium conditions, low heat flow implies that there is little or no crustal thickening under the basin. This feature could be the result of lithospheric folding, as may occur throughout Central Asia. Heat flow, geothermal gradients, geodynamical models, Lake Issyk Kul’, Tien Shan, Kyrghyzstan
Keywords: Heat flow; geothermal gradients; geodynamical model; Lake Issyk Kul'; Tien Shan; Kyrghyzstan